Prediction of risk and incidence of dry eye in critical patients - Diego Dias de Araújo; Natália Gherardi Almeida; Priscila Marinho Aleixo Silva; Nayara Souza Ribeiro; Andreza Werli-Alvarenga; Tânia Couto Machado Chianca (Universidade de São Paulo, 2016)
Objectives: to estimate the incidence of dry eye, to identify risk factors and to establish a risk prediction model for its development in adult patients admitted to the intensive care unit of a public hospital. Method: concurrent cohort, conducted between March and June, 2014, with 230 patients admitted to an intensive care unit. Data were analyzed by bivariate descriptive statistics, with multivariate survival analysis and Cox regression. Results: 53% out of 230 patients have developed dry eye, with onset mean time of 3.5 days. Independent variables that significantly and concurrently impacted the time for dry eye to occur were: O2 in room air, blinking more than five times per minute (lower risk factors) and presence of vascular disease (higher risk factor). Conclusion: dry eye is a common finding in patients admitted to adults intensive care units, and care for its prevention should be established.